2015
DOI: 10.1186/s13046-015-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting sphingosine kinase 2 (SphK2) by ABC294640 inhibits colorectal cancer cell growth in vitro and in vivo

Abstract: BackgroundColorectal cancer (CRC) is a major health problem in China and around the world. It is one of the leading causes of cancer-related deaths. Research groups are thus searching for novel and more efficient anti-CRC agents.ResultsHere we demonstrated that ABC294640, a novel SphK2 inhibitor, induced growth inhibition and apoptosis in transformed and primary CRC cells. The SphK activity was remarkably inhibited by ABC294640, accompanied by sphingosine-1-phosphate (S1P) depletion and ceramide incensement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 36 publications
1
79
0
Order By: Relevance
“…Increasing evidence suggests that alterations in SphK2 expression contribute to the pathogenesis of many human cancers [2931]. SphK2 overexpression in bladder cancer cells is closely implicated in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that alterations in SphK2 expression contribute to the pathogenesis of many human cancers [2931]. SphK2 overexpression in bladder cancer cells is closely implicated in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of SphK2 leads to decreased proliferation and enhanced chemosensitivity and apoptosis to gefitinib in non-small cell lung cancer [30]. The novel SphK2 inhibitor ABC294640 induces growth inhibition and apoptosis in transformed and primary colorectal cancer cells, suggesting that SphK2 may be involved in colorectal cancer development [31]. In this study, we found that SphK2 was a target gene of miR-613 and restoration of SphK2 expression abolished the inhibitory effect of miR-613 on cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…ABC294640 has been used extensively in vivo where it has shown some efficacy in animal models of solid tumours [50,98,113,114,116,118,124,125], blood cancers [36,37,121], and inflammatory conditions such as osteoarthritis [126], transplantation [120], stroke/ischemia [122,127] and colitis [128,129] (Table 2). It has been shown to dose-dependently decrease circulating S1P in mice [50] and S1P levels in xenograft tumours [50,112].…”
Section: Abc294640mentioning
confidence: 99%
“…Despite the off-targets, ABC294640 was found to sensitise cancer cells to chemotherapy [50,[114][115][116][117][118], Bcl-2 inhibitors [37], the Bcr-Abl inhibitor Imatinib and the proteasome inhibitor Bortezomib [36]. ABC294640 was found to reduce pro-proliferative signalling through the Akt and MAPK pathways via reduction in S1P receptor signalling.…”
Section: Abc294640mentioning
confidence: 99%
“…As summarized below, ABC294640 has therapeutic activity in diverse mouse tumor models both alone and in combination with other anticancer drugs (Antoon, White, Driver, Burow, & Beckman, 2012; Antoon et al, 2010; Antoon, White, et al, 2011; Beljanski et al, 2010; Beljanski, Knaak, et al, 2011; Beljanski, Lewis, et al, 2011; Dai et al, 2017; Dai, Smith, Foroozesh, Miele, & Qin, 2018; French et al, 2010; Qin et al, 2014; Schrecengost et al, 2015; Venant et al, 2015; Venkata et al, 2014; Wallington-Beddoe et al, 2014; Xu et al, 2018; Xun et al, 2015; Zhou, Chen, & Yu, 2018), as well as a number of rodent inflammation models (Fitzpatrick, Green, Frauenhoffer, et al, 2011; Fitzpatrick, Green, Maines, & Smith, 2011; Liu et al, 2012; Maines et al, 2008; Maines, Fitzpatrick, Green, Zhuang, & Smith, 2010; Maines et al, 2006; Poti et al, 2012; Shi et al, 2012) not discussed here. Additionally, ABC294640 diminished tumor incidence and multiplicity in the azoxymethane/dextran sulfate sodium model of colon carcinogenesis (Chumanevich et al, 2010).…”
Section: Sphingosine Kinase Inhibitorsmentioning
confidence: 99%